A model of firm heterogeneity in factor intensities and international trade - Emami Namini, Julian; Facchini, Giovanni; Lopez, Ricardo (Wiley, 2015)
Empirical evidence suggests that exporters – besides being more productive – are significantly more skilled labor intensive than non–exporters. In a setting which captures both these features, we show that the firm selection induced by trade liberalization works along two dimensions. First, export growth increases competition for skilled labor. This leads to the exit of some of the skilled labor intensive firms, while benefitting unskilled labor intensive ones. Second, within the group of firms with the same factor intensities, the reallocation of factors is towards the exporters. We show that the increased competition for skilled labor dampens the positive effect of trade liberalization on sector–wide TFP and real income.